Effectiveness of interleukin-1 receptor antagonist (Anakinra) on cerulein-induced experimental acute pancreatitis in rats. (September 2014) - Kaplan, Mustafa; Yazgan, Yusuf; Tanoglu, Alpaslan; Berber, Ufuk; Oncu, Kemal; Kara, Muammer; Demirel, Dilaver; Kucuk, Irfan; Ozari, Halil Onur; Ipcioglu, Osman Metin
Abstract Aim. Acute pancreatitis (AP) is defined as an inflammatory disease of the pancreas. The purpose of this study was to examine the effectiveness of Anakinra on cerulein-induced experimental pancreatitis rat model by using the results of biochemical and histopathological findings. Materials and methods. Cerulein was administered to induce AP in rats. Group 1 was the sham group. Subcutancerulein was injected to the rats in group 2 for experimental pancreatitis group. In groups 3 and 4, 100 and 50 mg/kg intraperitoneal Anakinra were injected after the induction of experimental pancreatitis by subcutaneous cerulein in rats, respectively. Lastly, in group 5, rats were injected with intraperitoneal saline and subcutan cerulean for placebo group. The following parameters were evaluated: histopathological score of pancreatitis, apoptotic index, amylase, lipase, TNF-α levels, IL-1β and the leukocyte count. Results. When the results of serum amylase, lipase, TNF-α and IL-1β levels, the leukocyte count, histopathologic scores and apoptotic indices of control group compared to the results of other groups, the differences exhibited statistical significance (all p < 0.05). On the other hand, when the results of fourth group compared with the results of third group, the data demonstrated statistical insignificance (p > 0.05). However, no any significant differences were found between the results of fourth and fifth groups (p > 0.05). Conclusion. In the light of these results, cerulein is an appropriate agent for experimental AP rat model and Anakinra has a favorable therapeutic effect on acute experimental pancreatitis model. Moreover, Anakinra significantly decreases cerulein-related pancreatic tissue injury and pancreatic apoptosis.